РЕШИТЕ УРАВНЕНИЕ : 2Х+1 3Х-2 Х + 1 _____ + 2 = _____ + _____ 3 2 3 БУДУ БЛАГОДАРЕН

РЕШИТЕ УРАВНЕНИЕ : 2Х+1 3Х-2 Х + 1
_____ + 2 = _____ + _____
3 2 3
БУДУ БЛАГОДАРЕН

  • вс уравнение приводим к общему знаменателю 3*2=6

    (2x+1)*2 (3x-2)*3 (x+1)*2

    ——- +(2)*6 = ——- + ————

    3 2 3

    4x+2+12=9x-6+2x+2 переносим неизвестное в лево , известное в право

    4x-2x-9x=-6+2-12-2

    -7x=-18

    x=-18:(-7)

    x=2 47

    47 -дробью

    Както так….

  • 2(2x+1)+12=3(3x-2)+2(x+1)

    4x+2+12=9x-6+2x+2

    18=7x

    x=18/7